Pengembangan Media Pembelajaran Berbasis Etnis Sumatera Utara - Uyuni Widiastuti; Adina Sastra Sembiring; Mukhlis Mukhlis (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2020)
The development of instructional media in this paper is the development of learning media used in learning Arts and Culture class X High School in Pangururan District, Samosir Regency. The learning media developed are invincible with the syllabus in class X, namely "presentation of musical works". The objectives of this study were to: (1) develop traditional Karo music learning videos; (2) Developing Karo traditional music learning textbooks. This research uses a Research & Development or research and development approach. The development of this learning media will be used by art teachers who are members of the MGMP (subject teacher deliberation) for Cultural Arts, especially art teachers in Pangururan District, Samosir Regency. The research conducted resulted in the development of instructional media in the form of learning videos for learning traditional Karo music and textbooks for learning traditional Karo music. The learning media developed in the form of learning videos for traditional Karo music includes the technique of playing Karo traditional music which is incorporated in the kulcapi drum ensemble whose instruments consist of kulcapi, keteng-keteng, and mangkuk. The next learning media is in the form of a textbook which contains the techniques for playing the kulcapi drum in the song Piso Surit and Terang Bulan. The two learning media that have been developed help the arts and culture teachers in carrying out the ethnicity of the ethnic North Sumatra.Keywords: Development, Learning Media, Ethnicity, North Sumatra